One pot biodiesel production from wet Chlorella vulgaris using supercritical methanol with oxide catalysts - masaharu, komiyama (2018)

(untitled)
The effect of heterogeneous catalyst in the supercritical methanol reaction of wet microalgae (64 wt% moisture content), Chlorella vulgaris, was examined in a batch operation system at 385°C for 60 minutes. The reaction products were separated into gas, liquid and solid products while the liquid product was the focus in this paper. Experimental results indicated that a-Al2O3 was the most plausible catalyst as it achieved the highest liquid product and FAME yield among the tested catalysts ZrO2, Zr(WO4)2 and catalyst-free reaction. It indicates that complete dewatering of feedstock, microalgae, may not be necessary in one pot biodiesel production, and the presence of heterogeneous catalyst promotes the yield of liquid product and FAME. © 2018 Author(s).